DELLAs Function as Coactivators of GAI-ASSOCIATED FACTOR1 in Regulation of Gibberellin Homeostasis and Signaling in Arabidopsis . Issue 7 (17th July 2014) - Fukazawa, Jutarou; Teramura, Hiroshi; Murakoshi, Satoru; Nasuno, Kei; Nishida, Naotaka; Ito, Takeshi; Yoshida, Michiteru; Kamiya, Yuji; Yamaguchi, Shinjiro; Takahashi, Yohsuke
Abstract : This work reports the discovery of the DELLA-binding transcription factor GAF1 and shows that DELLAs and TPR act as coactivators and a corepressor with GAF1, respectively. GA converts the GAF1 complex from transcriptional activator to repressor via degradation of DELLAs. Accordingly, DELLAs turn on or off two sets of GA-regulated genes by dual functions, namely titration and coactivation. Abstract: Gibberellins (GAs ) are essential regulators of plant development, and DELLAs are negative regulators of GA signaling. The mechanism of GA -dependent transcription has been explained by DELLA-mediated titration of transcriptional activators and their release through the degradation of DELLAs in response to GA . However, the effect of GA on genome-wide expression is predominantly repression, suggesting the existence of unknown mechanisms of GA function. In this study, we identified an Arabidopsis thaliana DELLA binding transcription factor, GAI-ASSOCIATED FACTOR1 (GAF1). GAF1 shows high homology to INDETERMINATE DOMAIN1 (IDD1)/ENHYDROUS. GA responsiveness was decreased in the double mutant gaf1 idd1, whereas it was enhanced in a GAF1 overexpressor. GAF1 binds to genes that are subject to GA feedback regulation. Furthermore, we found that GAF1 interacts with the corepressor TOPLESS RELATED (TPR) and that DELLAs and TPR act as coactivators and a corepressor of GAF1, respectively. GA converts the GAF1 complex from transcriptional activator to repressor via the degradation of DELLAs. These results indicate that DELLAs turn on or off two sets of GA -regulated genes via dual functions, namely titration and coactivation, providing a mechanism for the integrative regulation of plant growth and GA homeostasis.